Predictors of in-hospital mortality following intracerebral hemorrhage in East coast of Malaysia - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; Ab Rahman, Jamalludin; Abdul Rashid, Mohd Amran; Che Abdullah, Shahrin Tarmizi; Omar, Ahmad Marzuki; Mohd Shah, Azarisman Shah (2013)
Despite much medical progress, stroke remains a leading cause of death and disability. Physicians are faced with the task of predicting the likely outcome. The aim of our study was to analyze the frequency of various risk factors and determine predictors of in-hospital mortality among primary intracerebral hemorrhage(PICH)patients, thus providing insight in developing therapeutic strategies to improve the outcome.